Osajin from Maclura pomifera alleviates sepsis-induced liver injury in rats: biochemical, histopathological and immunohistochemical estimation - Alhilal, Mohammad; Erol, Huseyin Serkan; Yildirim, Serkan; Cakir, Ahmet; Koc, Murat; Celebi, Demet; Halici, Mesut Bunyami (Informa UK Limited, 2023)
This paper aimed to examine the impact of flavonoid osajin (OSJ) on liver damage induced by sepsis. A total of 30 male rats were divided into 5 groups (Sham, sepsis, OSJ 150, OSJ 300 and reference). During sepsis, elevated lipid peroxidation (LPO) level and catalase activity (CAT) and decreased glutathione (GSH) level and superoxide dismutase (SOD) activity were observed in hepatic tissues of sepsis group in comparison with Sham group. A strong interleukin-33 and caspase-3 expressions were detected in hepatic tissues of sepsis group. On the contrary, OSJ administration to OSJ 300 group showed a significant decrease (P < 0.001) in LPO level (176±2.926) and significant increase (P < 0.001) in GSH level (10.586±0.083) and SOD activity (29.152±0.094) in comparison with sepsis group (185.777±1.735, 8.246±0.124, 24.307±0.379 respectively). In addition, the consumption of OSJ reduced expressions of interleukin-33 and caspase-3 and improved histopathological integrity. In conclusions, OSJ has hepatoprotective effect against sepsis-induced liver injury.
Keywords: sepsis; Q1-390; Science (General); Liver; Liver; osajin; oxidative stress; sepsis; osajin; oxidative stress; 3. Good health